2018
DOI: 10.3389/fbioe.2018.00203
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Lysate Activates Human Subcutaneous Adipose Tissue Cells by Promoting Cell Proliferation and Their Paracrine Activity Toward Epidermal Keratinocytes

Abstract: Skin chronic wounds are non-healing ulcerative defects, which arise in association with a morbidity state, such as diabetes and vascular insufficiency or as the consequence of systemic factors including advanced age. Platelet Rich Plasma, a platelet-rich blood fraction, can significantly improve the healing of human skin chronic ulcers. Given that the subcutaneous adipose tissue is located beneath the skin and plays a role in the skin homeostasis, in this study, we investigated the in vitro response of human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Due to the high content in mitogenic growth factors, platelet products exert a strong proliferative stimulus on several in vitro cell cultures, as previously reported [14,15,30]. In this study, the proliferative trend demonstrated by doubling number and cyclin D1 protein levels were markedly higher in ACs-PL compared to ACs-FBS and similar between ACs-PL and CPCs-PL.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Due to the high content in mitogenic growth factors, platelet products exert a strong proliferative stimulus on several in vitro cell cultures, as previously reported [14,15,30]. In this study, the proliferative trend demonstrated by doubling number and cyclin D1 protein levels were markedly higher in ACs-PL compared to ACs-FBS and similar between ACs-PL and CPCs-PL.…”
Section: Discussionsupporting
confidence: 75%
“…PL treatment induced increased release or de novo secretion of some pro-inflammatory cytokines and chemokines by ACs. Indeed, it is well known from previous works that PL exerts an initial strong pro-inflammatory activity resulting in NF-κB activation and secretion of pro-inflammatory cytokines, events that are transient in order to prime certain defensive and reparative tissue mechanisms, then it inhibits and promotes resolution of the inflammatory phase [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional "acquired" factors occur after cell isolation and following processing. The composition of culture medium and supplements, substrate properties and oxygen concentration would most likely affect the features of MSCs through different mechanisms 16,17 . Therefore, the ideal way to compare the sources of MSCs in view of further clinical application should be based on the assessment of the specific properties of candidate cell types expanded in similar conditions, starting from the initial stages of cell processing.…”
mentioning
confidence: 99%